Bioética para estudantes de ciências biológicas: investigação sobre os fundamentos que compõem ou deveriam compor a área - Siebert, Paloma Rodrigues [UNESP] (2015)
Although it is a common curricular component in undergraduate courses related a health, recognizing the importance of bioethics in the formation of biologists and biology teachers is recent. The considerable increase of information related to Life Sciences and biotechnology applications of this knowledge significantly increase the need of bioethics being understood as an essential component in undergraduate programs in Biology. Such demand is already appearing in some curricular reforms for the Life Science courses, however these initiatives, althrough of great importance in itself does not solve the ethical training of professionals trained in these courses. The following step would be to reflect on how this training will be given. So or premise research was to gather researchers in the field to answer the questions we have prepared for the definition of what we can Bioehics Education. This was the challenge presented to us a research to compose this doctoral thesis. Therefeore, our objectives were: a) Raise the fundamentals that can make training in Bioethics in graduates of training courses and graduates in Biological Sciences; b) To analyze the contributions from researchers interviewed to identify assumptions that should make up the area of Bioethics; c) Gather theoretical and metodological indications for the establishement of a discipline or training axes in Bioethics; d) List the possible difficulties for the insertion and development of a discipline or training axes in Bioethics in undergraduate courses in Biological Sciences. To develop this work, we have adopted as the metodological foundation Applied Qualitative Research. The data were collected through the delopment of an open questionnaire sent by e-mail do prestigious national and international researchers in the bioethics area. After we receive the responses, we organize data into categories of analysis. The results were used along with the literature, to develop lines of...